2022
DOI: 10.1177/0734371x221084104
|View full text |Cite
|
Sign up to set email alerts
|

Wellbeing During a Crisis: A Longitudinal Study of Local Government Civil Servants

Abstract: The COVID-19 crisis has affected numerous areas of civil servants’ working life. We investigate, using the JD-R model, the impact of the current crisis on civil servants’ wellbeing. Furthermore, we argue that the COVID-19 pandemic might have different consequences for civil servants with various role perceptions. We distinguish between traditional, NPM, and NPG civil servants. A longitudinal survey ( N = 569) has shown that: (a) wellbeing decreased over a 6-months period; (b) job demands, including work pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 69 publications
0
14
0
Order By: Relevance
“…The measurement scales are also useful for practitioners as they can be applied to a number of key HRM processes, for example, for recruitment and selection by providing insight into the profiles of candidates and help create a diversity of roles in the workforce (Schnell & Gerard, 2022). The scales can be used for training and development by having civil servants reflect on the role(s) they identify with, to improve certain roles, and to learn how new values and behaviors can be promoted (van der Meer et al, 2022). This attention to different role perceptions is important to ensure that having a mix of civil servants with various role perceptions can become a strength.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The measurement scales are also useful for practitioners as they can be applied to a number of key HRM processes, for example, for recruitment and selection by providing insight into the profiles of candidates and help create a diversity of roles in the workforce (Schnell & Gerard, 2022). The scales can be used for training and development by having civil servants reflect on the role(s) they identify with, to improve certain roles, and to learn how new values and behaviors can be promoted (van der Meer et al, 2022). This attention to different role perceptions is important to ensure that having a mix of civil servants with various role perceptions can become a strength.…”
Section: Discussionmentioning
confidence: 99%
“…Existing studies that focused on civil servants’ roles have had several shortcomings. For instance, they are often normative in nature, suggesting what roles civil servants should take without providing empirical evidence (e.g., Brandsen & Honingh, 2013; Peters, 2010; Rhodes, 2016), or they use methods that limit possibilities for systematic analysis and generalization, such as the Q‐methodology (e.g., Selden et al, 1999; van der Steen et al, 2018) or short item measurements (van der Meer et al, 2022).…”
mentioning
confidence: 99%
“…The challenges experienced by public sector employees also differ from one public administration to another. For example, Van der Meer et al (2022) found that work pressure and work–life imbalance increased burnout among civil servants working for a large municipality in the Netherlands during the pandemic. They pointed out that the work–life imbalance and work pressure increase burnout among civil servants because they were forced to work from home and, at the same time, schools and nurseries were closed during the first part of the COVID-19 pandemic.…”
Section: Toward a Contingent Human Resource Management Approach Of Te...mentioning
confidence: 99%
“…In addition, during the pandemic, civil servants, education, and health care personnel faced specific challenges. In the public service, working from home and school closures have threatened work–life balance (Van der Meer et al, 2022). In the education sector, the new tasks related to online teaching are associated with increased workload, which could negatively affect teachers’ perception of telework (Allen et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…From a policing scholarship perspective, this paper provides valuable insights into challenges related to alternatives to traditional police officers (Bittner 1990; Muir 1979). Today, cities increasingly look to alternatives to traditional police officers and face pressures to expand the role of officers in community-oriented ways (Cheng 2022; Gascón and Roussell 2019; Gordon 2022).…”
Section: Introductionmentioning
confidence: 99%